Tax Avoidance, Tax Risk, and Firm Value: Evidence from Indonesia’s Consumer Non-Cyclicals Sector - Putri, Alivia; Dewi, Siti Ratna Sari (Manunggal Halim Jaya, 2026)
This study examines the influence of tax avoidance and tax risk on firm value among companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Using a quantitative approach and panel data regression analysis, the research observes 16 firms (80 firm-year observations) selected through purposive sampling based on data completeness and consistent profitability. The findings show that tax avoidance and tax risk jointly exert a significant effect on firm value, confirming that corporate tax behavior plays a critical role in shaping investor perception and market valuation. In partial testing, tax avoidance has a significant positive impact on firm value, indicating that efficient tax strategies are perceived as value-enhancing when aligned with managerial prudence and compliance. Conversely, tax risk does not exhibit a statistically significant effect, suggesting that the market does not fully penalize fiscal uncertainty when disclosure and governance mechanisms are adequate. These results imply that firms must balance tax efficiency with transparency to maintain investor confidence and sustainable performance. The study contributes to the literature on corporate governance, taxation, and financial policy by providing empirical evidence on how tax-related decisions influence firm value within an emerging market context.